Knowledge of Diabetes Risk Factors among Market Women in Orisunbare Osogbo, Osun State, Nigeria - Adeola Oluwaseun Oshineye; Chinenye Christiana Ukenyi; James Ebun Atolagbe (Pan-African Journal of Health and Environmental Science, 2023)
Background: Diabetes is a life-threatening disease that has become a global threat to public health. Hence, it is a fast-growing chronic disease that affects not only diabetic patients, but also society at large. This study examined the level of knowledge about diabetes risk factors among market women in Orisunbare Osogbo, Osun State, Nigeria.